2019
DOI: 10.3892/or.2019.6999
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein disulfide isomerase�A3 and its clinicopathological association in gastric cancer

Abstract: Protein disulfide isomerase A3 (PDIA3) is a chaperone protein that supports the folding and processing of synthesized proteins. Its expression is associated with the prognosis of laryngeal cancer, hepatocellular carcinoma, diffuse glioma and uterine cervical cancer. In the present study, the expression levels of PDIA3 and its clinicopathological association were examined in 52 cases of gastric cancer (GC). The expression of PDIA3 was examined by immunohistochemistry and scored using a semi-quantitative method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…PDIA3 expression level is correlated with the clinical outcome of patients with ovarian carcinoma who receive chemoradiotherapy, and the sensitivity to paclitaxel can be enhanced by PDIA3 silencing [47, 48]. In ESCC, we found that PDIA3 decreased gradually with the progress of stage and related to favorable prognosis, which was in accord with the findings in gastric cancer [49], but contrary to those in hepatocellular carcinoma [50]. The favorable prognostic value of PDIA3 in ESCC implies that ESCC patients with high expression of PDIA3 may be more sensitive to chemotherapy such as paclitaxel, but further studies are warranted.…”
Section: Discussionsupporting
confidence: 70%
“…PDIA3 expression level is correlated with the clinical outcome of patients with ovarian carcinoma who receive chemoradiotherapy, and the sensitivity to paclitaxel can be enhanced by PDIA3 silencing [47, 48]. In ESCC, we found that PDIA3 decreased gradually with the progress of stage and related to favorable prognosis, which was in accord with the findings in gastric cancer [49], but contrary to those in hepatocellular carcinoma [50]. The favorable prognostic value of PDIA3 in ESCC implies that ESCC patients with high expression of PDIA3 may be more sensitive to chemotherapy such as paclitaxel, but further studies are warranted.…”
Section: Discussionsupporting
confidence: 70%
“…However, ERp57 exerts the opposite effect on gastric cancer progression; its expression is significantly decreased in gastric cancer and metastases, and low levels of ERp57 are correlated with an increased depth of tumor invasion and advanced disease stage [37]. The results of retrospective analysis have shown that high expression indicates favorable overall survival in gastric cancer patients [38]. ERp57 is also related to gastric cancer treatment.…”
Section: Clinical Implications Of Erp57 In Cancermentioning
confidence: 99%
“…Liver cancer with high PDIA3 expression follows an unfavorable course and is characterized by high proliferation activity and a low frequency of cell death. The expression of PDIA3 and its association with prognosis has been reported for other carcinomas (21,22,(38)(39)(40)(41). Furthermore, knock-down of PDIA3 may enhance the effect of radiation therapy in laryngeal cancer (38) and breast cancer (42).…”
Section: Discussionmentioning
confidence: 82%